Knowledge Authority and Power Relations in Digital Non-Formal Education: A Foucaultian Perspective on Alternative Learning Spaces - Wicaksono, Ridlo Febi; Karsidi, Ravik (Universitas Muhammadiyah Sumatera Utara (UMSU), 2025)
This study examines how digital non-formal education platforms shape knowledge authority and power relations in the Indonesian context. Qualitative case studies of educational YouTube, national online courses, and global platforms have been conducted using content observation, documentation, and critical discourse analysis based on Foucault's theory. The results of the study show that the legitimacy of knowledge shifts from academic authority to popularity metrics and algorithmic logic. Algorithms, gamification, and certification schemes function as disciplinary mechanisms that guide learning behavior while recording user data. Learning subjects are constructed as independent and productive individuals, but also as consumers and data commodities. The conclusion of the study confirms that claims of inclusivity in digital education are partial because inequality of access and digital literacy continue to create new exclusions, while knowledge is spread fragmentarily outside the formal curriculum.